Solvency Management and Firm Growth of Listed Non-Financial Firms in Nigeria - Esiyeden, Anita Roli; Uagbale-Ekatah, Rosemary Edememen (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study investigates the effect of solvency management on the growth of listed non-financial firms in Nigeria. Adopting an ex-post facto research design, the study utilized panel data from 73 non-financial firms listed on the Nigerian Exchange Group between 2020 and 2024. Short-term solvency management (liquidity) was measured using the current ratio, while long-term solvency management was proxied by the total liabilities-to-assets ratio. Firm growth, the dependent variable, was assessed using changes in profit after tax (PAT), with firm size included as a control variable. Panel least squares regression was employed for data analysis. The results revealed that both short-term solvency management (liquidity) and long-term solvency management have positive but statistically insignificant effects on firm growth. The study concludes that while financial soundness contributes to firm stability, it does not significantly drive growth. It is recommended that firms integrate short-term solvency management (liquidity) and long-term solvency management with broader strategic investment decisions to achieve sustainable growth.